PROBLEM OF THE VERBALIZERS OF CONCEPT OF “MAN” IN MODERN LINGUISTICS (Academicia Globe: Inderscience Research, 2021)
The concept of “man” is used in different places with different meanings. If we investigate about the verbalizers of the concept of “man”, we can say that this word is widely used in different spheres of Linguistics.